La relación representativa desde la percepción de los electores (Representative relationship from the perception of voters) - Treviño Terán, José Alejandro; Lozano Treviño, David Fernando; Barragán Codina, José Nicolás (Facultad de Contaduría Pública y Administración, 2015)
Abstract: This paper details a way of measuring the relationship between representatives and represented in a modern democratic model. It identifies the problems perceived by the citizen to determine if he or she considers that a representative: addresses the problems; if he or she is looking to meet individual or collective interests and if it´s doing effectively. It´s planned to conduct evaluation for the government’s political performance from key stakeholder that are the citizen. Also, it allows us to make a constant evaluation of the quality of not only maintain political representation at election time, but since the beginning of management representative determined.